The ontogeny of synovial tissue macrophages - Hutton, Joseph; Sun, Wenrui; Hasegawa, Tetsuo (Frontiers in Immunology, 2025)
Macrophages are essential components of all body tissues, including the synovium. Tissue macrophages originate either from embryonically seeded “primitive” macrophages or from bone marrow-derived monocytes. In adults, both sources contribute to macrophage populations, with their relative proportions varying across tissues and between steady-state and inflammation. Macrophages are highly responsive to microenvironmental and signalling cues, which significantly influence their function within tissues. This article reviews the current understanding of synovial tissue macrophage ontogeny in health and disease, highlighting knowledge gaps and potential avenues for future research.